HYDATID CYST OF THE ORBIT - Awan, A. Aziz; Mufti, Tariq; Akhtar, Saleem (Journal of Ayub Medical College Abbottabad, 1990)
Hydatid cyst is the larval stage of dog tapeworm, Echinococcus Granulosis. Human infection occurs from ingestion of water and green vegetable contaminated with dog faeces and by handling infected dogs and ungulates. Although hydatid cyst has been reported to develop in any organ of the body but 90% of the disease occurs in the liver and lungs. Other organs such as brain, bone, and rarely orbit and soft tissue may be involved. Intra-orbital hydatid cyst gradually enlarges causing progressive proptosis, disk oedema, diplopia, exposure keratitis and if untreated to irreversible visual loss. Pre-operative diagnosis in spite of host of available diagnostic facilities is not always conformity. The present case offered similar diagnostic dilemma. Surgical resection of the cyst is the treatment of choice with the post-operative course of Mebendazole.